-Convergence Problems for Asymptotically Nonexpansive Mappings in CAT(0) Spaces - Luo Yi Shi; Ru Dong Chen; Yu Jing Wu (Abstract and Applied Analysis)
New △-convergence theorems of iterative sequences for asymptotically nonexpansive mappings in CAT(0) spaces are obtained. Consider an asymptotically nonexpansive self-mapping of a closed convex subset of a CAT(0) space . Consider the iteration process , where is arbitrary and or for , where . It is shown that under certain appropriate conditions on   △-converges to a fixed point of .